INFLUENCE OF GLOBAL POSTURAL REEDUCATION IN VERTICAL JUMP IN FEMALE HANDBALL. PILOT STUDY (Cuestiones de Fisioterapia, 2016)
Aim: the aim of this study was to determine the usefulness of Global Postural Reeducation® (GPR) compared with static stretching to improve vertical jump measured in flying time and jump height in female handball players.Material and method: a sample of 13 women was selected and divided into two randomized groups, one treated with GPR, and the other one treated with static stretching. Squat Jump (SJ), Counter Movement Jump (CMJ) and Abalakov Jump (AJ) was measured before and after our intervention. Results: significant reduction was observed in flying time on Abalakov Jump after treatment with GPR. No significant improvement was observed in SJ nor CMJ in flying time nor jump height. Static stretching had no significative results in any of the variables measured on AJ, SJ o CMJ.Conclusion: GPR and static stretching seem to have no immediate effect when using them before physical activity, not increasing performance at flying time measured at SJ and CMJ. GPR seems to have negative effects on flying time at AJ. Otherwise, static stretching does not have effects on flying time at AJ. In vertical jump height, GPR and static stretching seem to have no effect at SJ, CMJ and AJ performance.